Heusler nanoparticles for spintronics and ferromagnetic shape memory alloys - Wang, Changhai; Meyer, Judith; Teichert, Niclas; Auge, Alexander; Rausch, Elisabeth; Balke, Benjamin; Huetten, Andreas; Fecher, Gerhard H.; Felser, Claudia (Journal of Vacuum Science & Technology B, Nanotechnology and Microelectronics, 2014)
Heusler nanoparticles emerge as a new class of multifunctional materials. In this critical review, the latest progress in studies on Heusler nanoparticles is summarized. The authors discuss their structural and physical properties interesting for research fields such as spintronics and ferromagnetic shape memory alloys. As a young research field, the majority of studies on Heusler nanoparticles focus on their synthesis, structure, and magnetic characterizations. Important issues such as size dependent structure, phase transition, magnetic, and spin-related properties are still open. Further investigations are needed to verify the technical significance of Heusler nanoparticles for practical applications such as data storage, magnetic sensors, and microactuators. © 2014 American Vacuum Society.
CRIS-Team Scopus Importer:2023-03-20